Autoimmune/autoinflammatory syndrome induced by adjuvants: what is it and why the controversy? - Sajal Ajmani (Indian Journal of Rheumatology)
Autoimmune/autoinflammatory syndrome induced by adjuvants (ASIA) is a group of autoimmune diseases with possible adjuvant-associated causes, such as siliconosis, macrophagic myofasciitis syndrome, Gulf War syndrome, sick building syndrome, and postvaccination autoimmune phenomena. Over time, an international registry with over 500 patients has been established for this conglomeration of rare syndromes. In spite of this, the very existence of ASIA has been debated at times and the diagnostic criteria have come under criticism. The cause-effect relationship between adjuvants and autoimmune phenomenon is difficult to prove due to lack of precisely defined time range between exposure and disease and also due to numerous exposures to adjuvants a person may have in his or her lifetime. The current article attempts at reviewing the clinical features, diagnostic criteria, and evidence for/against the existence of the disease.